Effects of temperature on the hydrotreatment behaviour of pyrolysis bio-oil and coke formation in a continuous hydrotreatment reactor - Gholizadeh, M.; Gunawan, R.; Hu, X.; De Miguel Mercader, F.; Westerhof, R.; Chaitwat, W.; Hasan, M.; Mourant, D.; Li, Chun-Zhu (Elsevier, 2016)
In this study, we investigated the effects of temperature on the hydrotreatment behaviour of bio-oil from the pyrolysis of mallee wood with a special focus on coke formation. The experiments were carried out in a continuous hydrotreatment reactor with pre-sulphided NiMo/γ-Al2O3 as the main catalyst over a nominal temperature range from 375 to 450 °C while the outlet pressure was set at 70 bar. GC-MS, TGA, UV-Fluorescence spectroscopy, elemental analysis and FT-Raman spectroscopy were used to characterise the reaction products and spent catalyst. While an upstream Pd/C catalyst bed had some effects of stabilising bio-oil, it was insufficient to ensure long-term operation under all conditions. Aromatic ring growth and polymerisation could take place continuously even under the overall dominating hydrotreatment/hydrocracking conditions. Temperature drastically affected the hydrotreatment product quality and coke formation. Increasing temperature favours the polymerisation for the formation of coke. At high temperature (e.g. 450 °C), the coke formation could be so severe that the reactor was blocked before the heavy liquid could reach the end of the reactor. The coke formed mainly from heavy liquid showed very different properties (different aromatic ring systems) from the coke formed mainly from the light species.